Interaksi Sosial Remaja Pasca Rehabilitasi Narkoba di Nagari Paninjauan Kecamatan X Koto, Kabupaten Tanah Datar - Septianto, Dio; Kamal, Muhiddinur (Lembaga Yasin AlSys, 2023)
Social interaction is something that teenagers need. Driven by high curiosity, this often leads to negative impacts such as drug abuse. One of the cases occurred in Nagari Paninjauan, a teenager finally fell into legal custody to go through the rehabilitation process. Even though they have been responsible for their actions, society's view of teenagers is still considered bad, causing gaps in their social interactions, so this is very interesting to research. The aim of this research is to find out the background and interactions of teenagers before they are introduced to drugs and to find out the form of their interactions after drug rehabilitation. This study used descriptive qualitative method. Data collection was carried out through observation and interviews with an informant. Based on the results of this research, it is known that informants who initially interacted actively in society, were ultimately influenced by their friendship environment to consume and sell drugs. However, after serving a sentence and training for five years and three months, the informant still received bad views from the public. Currently, the form of interaction that teenagers have is accommodation. Existing conditions also cause teenagers to tend to be passive in interacting with society. Thus, researchers suggest to informants to open themselves up and try to develop their potential so that society's view of them changes.